2017
DOI: 10.1155/2017/2696071
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulating Enzymes and Connected MicroRNA Regulators Have Prognostic Value in Classical Hodgkin Lymphomas

Abstract: There are no previous studies assessing the microRNAs that regulate antioxidant enzymes in Hodgkin lymphomas (HLs). We determined the mRNA levels of redox regulating enzymes peroxiredoxins (PRDXs) I–III, manganese superoxide dismutase (MnSOD), nuclear factor erythroid-derived 2-like 2 (Nrf2), and Kelch-like ECH-associated protein 1 (Keap1) from a carefully collected set of 41 classical HL patients before receiving any treatments. The levels of redoxmiRs, miRNAs known to regulate the above-mentioned enzymes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…However, Keap1 and Nrf2 mRNA levels in malignant cells and adjacent pancreatic tissue do not seem to play a major prognostic role or be associated with disease aggressiveness. Furthermore, the strong correlation between Nrf2 and Keap1 mRNA levels seen here in both the malignant and the adjacent benign areas, and previously in Hodgkin lymphomas [15], seems to point out a disturbance in regulatory events, likely at the protein level. Kosti et al [25] recently compared extensive mRNA and protein data in various cancer types.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, Keap1 and Nrf2 mRNA levels in malignant cells and adjacent pancreatic tissue do not seem to play a major prognostic role or be associated with disease aggressiveness. Furthermore, the strong correlation between Nrf2 and Keap1 mRNA levels seen here in both the malignant and the adjacent benign areas, and previously in Hodgkin lymphomas [15], seems to point out a disturbance in regulatory events, likely at the protein level. Kosti et al [25] recently compared extensive mRNA and protein data in various cancer types.…”
Section: Discussionsupporting
confidence: 74%
“…Expression levels of miRNAs are profoundly altered during carcinogenesis, but alterations in miRNA profiles may also initiate tumour growth and metastasis [12, 13]. Some miRNAs are considered to be “redoxmiRs,” as they have an essential influence on redox-state regulation [14, 15]. For example, miR-93 has been shown to directly repress Nrf2 mRNA [16].…”
Section: Introductionmentioning
confidence: 99%
“…LIPCAR is a novel biomarker of cardiac remodeling and predict future death in patients with HF 24 , suggesting potential interest of non-coding RNAs as biomarkers in molecular diagnostics. SOD2 mRNA was recently reported for predicting worse prognosis of patients with untreated classical Hodgkin lymphoma 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Such ROS accumulation induces cellular damage that may promote cancer development as well as its metabolic phenotype [ 13 - 15 , 27 ]. In fact, most of the studies about SOD2 expression and cancer have shown that overexpression of this enzyme is associated with the presence of metastases and poor prognosis in many malignancies, such as lymphomas [ 28 , 29 ], glioblastoma [ 30 ], bladder [ 31 ], lung [ 32 ], colorectal [ 33 ], breast [ 34 ], penile [ 35 ], gastric [ 36 ], esophageal [ 37 ] and oral cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%